Oral history and historical writing among Arabs - Critical Analytical Study – - Louis, Balqis Edan (Journal of Humanities & Social Sciences, 2021)
The aim of the study is to demonstrate the efforts of Muslim historians in preserving oral history and making it an important foundation of the historical material. The inductive syllabus was used in the study, and the results of it showed that the early historians adopted a set of characteristics and controls that are compatible with the nature of Islamic history, and these things in its entirety participated in the emergence of the curriculum Criticism of historical narratives, and in light of the results, a number of recommendations and proposals were presented to study oral history, preserve it, and develop ways of adopting it.